Model checking CSPZ: Techniques to overcome state explosion - MOTA, Alexandre Cabral (2001)
Cabral Mota, Alexandre; Cezar Alves Sampaio, Augusto. Model checking CSPZ: Techniques to overcome state explosion. 2001. Tese (Doutorado). Programa de Pós-Graduação em Ciência da Computação, Universidade Federal de Pernambuco, Recife, 2001.